2017
DOI: 10.1155/2017/3276120
|View full text |Cite
|
Sign up to set email alerts
|

Appendectomy as a Risk Factor for Bacteremic Biliary Tract Infection Caused by Antibiotic-Resistant Pathogens

Abstract: Background/Aims Recent evidence has suggested that appendix plays a pivotal role in the development and preservation of intestinal immune system. The aim of this study is to examine whether prior appendectomy is associated with an increased risk for the development of antibiotic-resistant bacteria in bacteremia from biliary tract infection (BTI). Methods Charts from 174 consecutive cases of bacteremia derived from BTI were retrospectively reviewed. Using multivariate analysis, independent risk factors for deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
0
9
0
5
Order By: Relevance
“…There is therefore a critical need to identify, at the bedside, which patients are at high risk for infection with multidrug-resistant pathogens, so that initial empiric therapy can be targeted at these patients without adversely affecting the rest of the patients with BTI. Unfortunately, many previous studies[ 6 7 12 13 ] have only identified a few risk factors that lead to multidrug-resistant bacterial infections in BTI patients, but no model has been constructed to predict the probability of multidrug-resistant bacterial infections in individual patients. We used a nomogram to build a simple, convenient and repeatable bedside prediction tool which predicts multidrug-resistant bacteria infection and differentiates low versus high risk patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is therefore a critical need to identify, at the bedside, which patients are at high risk for infection with multidrug-resistant pathogens, so that initial empiric therapy can be targeted at these patients without adversely affecting the rest of the patients with BTI. Unfortunately, many previous studies[ 6 7 12 13 ] have only identified a few risk factors that lead to multidrug-resistant bacterial infections in BTI patients, but no model has been constructed to predict the probability of multidrug-resistant bacterial infections in individual patients. We used a nomogram to build a simple, convenient and repeatable bedside prediction tool which predicts multidrug-resistant bacteria infection and differentiates low versus high risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…These five predictors are easy to obtain in clinical practice, even in developing countries, indicating that the model has a wide range of application. In the present study, the previous antibiotic use within 90 days and previous biliary surgery were not statistically significant in univariate analysis, but based on clinical experience and prior reports[ 5 6 7 12 13 ] we included these in the multivariate analysis. The results of multivariate analysis showed that previous antibiotic use within 90 days and previous biliary surgery were independent risk factors for multidrug-resistant bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, increasing evidence has revealed that the human appendix plays important biological roles in regulating the intestinal immune system and microbiome ( Randal Bollinger et al, 2007 ; Laurin et al, 2011 ; Masahata et al, 2014 ; Kooij et al, 2016 ; Girard-Madoux et al, 2018 ; Vitetta et al, 2019 ). Moreover, studies suggest that prior appendectomy may be associated with increased risk of many diseases, such as sarcoidosis, antibiotic-resistant bacteria-mediated bacteremia caused by biliary tract infection, gallstones, pyogenic liver abscesses, gastrointestinal cancers, Parkinson’s disease (PD), and rheumatoid arthritis ( Tzeng et al, 2015 ; Chung et al, 2016 ; Liao et al, 2016 ; Song et al, 2016 ; Kawanishi et al, 2017 ; Sawahata et al, 2017 ; Rubin, 2019 ). However, other studies have indicated no overall increase in cancer incidence several years after appendectomy ( Mellemkjaer et al, 1998 ; Cope et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%